Bankruptcy Legal System Reform in Settlement of Debtors’ Debt According to the Bankruptcy law - Basri, Herlina; Santiago, Faisal; Zuwanda, Rifka; Yusuf, Hudi; Samiyono, Sugeng (Faculty of Law, Andalas University, 2024)
According to Law No. 37 of 2004, bankruptcy is the complete seizure of a bankrupt debtor's assets, with the curator managing and settling them under the watchful eye of a supervising judge. There are several conditions for a debtor to be declared bankrupt, including having two or more creditors and not being able to make payments of at least one debt that is due and collectible and can be at his request or the request of one or more creditors. This article discusses the principle of distributing the debtor's assets if a debtor is declared bankrupt. According to Bankruptcy Law Regarding creditor provisions, in bankruptcy, three creditors are guaranteed compensation; the first is a separatist creditor, namely the creditor holding a material guarantee, then the preferred creditor, who has the right to precede because of the nature of his receivables by law is given a special position, and the last is a concurrent creditor—specifically, creditors who do not fall under the categories of favored and separatist creditors. After Article 2 paragraph (1) is explained, it is determined that creditors are concurrent, separatist, and preferential. Separatist and preferred creditors can apply for a declaration of bankruptcy without losing collateral rights to their assets on the debtor's assets and their right to take precedence. The debtor’s assets will eventually be distributed by the portion of the amount of the creditor's credit. This bankruptcy principle means that the debtor's property is jointly guaranteed for all creditors divided according to the principle of balance or “Pari Pasu Prorata Parte”